Perù frontiera del mondo. Eielson e Vargas Llosa: dalle radici all'impegno cosmopolita / Perú frontera del mundo. Eielson y Vargas Llosa: de las raíces al compromiso cosmopolita - Canfield, Martha Luana (Biblioteca di Studi di Filologia Moderna, 2013)
Jorge Eduardo Eielson (Lima 1924 - Milan 2006) and Mario Vargas Llosa (Arequipa, Peru, 1936; Winner of the Nobel prize in 2010) are certainly two 'exemplary Peruvians', as they have both started by digging into the history and social conflicts of their country, before opening up to global culture and reality with an interdisciplinary and intercultural spirit: Vargas Llosa did so using fiction, theatre, non-fiction and journalism; Eielson used poetry, the visual arts, non-fiction and journalism. The volume offers a rich itinerary starting from an interview with Vargas Llosa by José Miguel Oviedo (Florence, 2008), and then goes through individual aspects of the work by the two authors. It is then accompanied by photographic records and a DVD with an elaboration of Eielson's visual works, paintings and poems.